2011
DOI: 10.1063/1.3656432
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the origin of the memory effect in metal/organic semiconductor/metal structures

Abstract: We report on the resistive switching effect in metal/organic semiconductor/metal structures and present a general explanation of the switching mechanism in these devices. The J-V characteristics of metal/tris(8- hydroxyquinolinato)aluminum (Alq3)/metal devices will be discussed and it will be further shown that these sustain only a limited number of switching cycles. Besides Alq3, we also investigate other organic semiconductor materials and obtain a bistable behavior, which is independent of the organic mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The resistance values for the high-resistance state (HRS) and the low-resistance state (LRS) are calculated from the curve linear best-fit (dashed lines); R LRS $ 2:8 Â10 5 X and R HRS $ 4:9Â10 2 X. Sebastian et al reported on a conceptually identical device (ITO/a-NPD/Al). 29 Accordantly, the impedance spectroscopy analysis reveals the filamentary nature of the switching.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The resistance values for the high-resistance state (HRS) and the low-resistance state (LRS) are calculated from the curve linear best-fit (dashed lines); R LRS $ 2:8 Â10 5 X and R HRS $ 4:9Â10 2 X. Sebastian et al reported on a conceptually identical device (ITO/a-NPD/Al). 29 Accordantly, the impedance spectroscopy analysis reveals the filamentary nature of the switching.…”
mentioning
confidence: 97%
“…28,29 The layer of a-NPD had the same nominal thickness (120 nm) as the previous devices. No metal NPs were intentionally introduced within the a-NPD film.…”
mentioning
confidence: 99%
“…Therefore, with the rapid develop-52 ment of organic memory technology, a lot of effort has been made 53 to improve organic memory device structures and to understand 54 their operating mechanisms. 55 A number of device structures of the nonvolatile organic memory 56 have been manufactured and extensively explored, such as a single-57 layer structure consisting of only one type of organic material [5,6], a 58 tri-layer structure in which nano-traps for charge carriers are sand- 59 wiched between two organic layers [7,8], and a spin-cast blend of 60 polymer and nano-traps in which nano-traps are randomly dis- 61 persed in the polymer layer [9][10][11][12][13][14][15][16]. Because the charges stored 62 inside the nano-traps can efficiently change the conductivity of 63 the organic layer, finding appropriate materials to produce the 64 nano-traps has been the major issue in the tri-layer or hybrid com-65 posite structures of the organic memory.…”
mentioning
confidence: 99%
“…A complete overview on materials and architectures can be found in recent reviews [12,13]. RS mechanism in OMDs has been attributed to very different phenomena, based on charge injection/trapping mechanisms [14][15][16][17], or the formation of conductive filaments (CFs) [18][19][20][21][22][23][24]. Filaments were argued to be based on metallic [25], or carbon rich [26] dendritic paths.…”
Section: Introductionmentioning
confidence: 98%